Requirement of prorenin receptor and vacuolar H+-ATPase-mediated acidification for Wnt signaling - Sirrenberg-Cruciat, Cristina-Maria; Ohkawara, Bisei; Acebron, Sergio P.; Karaulanov, Emil; Reinhard, Carmen; Ingelfinger, Dierk; Boutros, Michael; Niehrs, Christof (Science, 2010)
Wnt/beta-catenin signaling is important in stem cell biology, embryonic development, and disease, including cancer. However, the mechanism of Wnt signal transmission, notably how the receptors are activated, remains incompletely understood. We found that the prorenin receptor (PRR) is a component of the Wnt receptor complex. PRR functions in a renin-independent manner as an adaptor between Wnt receptors and the vacuolar H+-adenosine triphosphatase (V-ATPase) complex. Moreover, PRR and V-ATPase were required to mediate Wnt signaling during antero-posterior patterning of Xenopus early central nervous system development. The results reveal an unsuspected role for the prorenin receptor, V-ATPase activity, and acidification during Wnt/beta-catenin signaling.
Im Titel ist "+" hochgestellt
Gesehen am 19.07.2023